Systemic Lupus Erythematosus (SLE) and Antineutrophil Cytoplasmic Antibody-Associated Vasculitis (AAV) Overlap Syndrome: Case Report and Review of the Literature - Sathish Itikyala; Debendra Pattanaik; Syed Raza (Case Reports in Rheumatology)
We report here the first case of systemic lupus erythematosus (SLE) and antineutrophil cytoplasmic antibody-associated vasculitis overlap syndrome (SLE/AAV) who had granulomatous polyangiitis (GPA) as the initial presentation. SLE/AAV overlap syndrome is an uncommon entity recently described in the literature. Prior reported patients with SLE/AAV overlap syndrome presented with SLE and microscopic polyangiitis (MPA). Our patient initially presented with granulomatous gastric ulcer and later developed respiratory failure. She was diagnosed with GPA. While on maintenance treatment with azathioprine 150 mg/day, she developed hematuria and proteinuria which turned out to be from class V lupus nephritis instead of relapse of vasculitis. Currently, the patient is doing well after treatment with rituximab. Although rare, this entity should be recognized and need to be treated appropriately.